Comparison of the Effects of Sugammadex Recommended Dose (2 mg/kg) and Fixed Dose of 200 mg on the Reversal of Moderate Neuromuscular Block and Recovery Profile in Adult Patients - Ji-Yoon Jung; Sung-Ae Cho; Woojin Kwon; Hongwook Kim; Tae-Yun Sung (Medicina)
Background and Objectives: Neuromuscular blocking agents are essential to ensure optimal surgical conditions during general anesthesia. Sugammadex, a selective binding agent, is widely used to reverse neuromuscular blockade. While weight-based dosing (2 mg/kg for moderate blockade) is recommended, many clinicians administer a fixed dose of 200 mg in clinical practice, potentially leading to overdosing. This study aimed to compare the efficacy and recovery profiles of weight-based and fixed-dose sugammadex in patients undergoing general anesthesia. Materials and Methods: In this randomized controlled trial, 20 patients were divided into two groups: the recommended dose group (R group, 2 mg/kg) and the fixed dose group (F group, 200 mg). Primary outcomes included time to achieve a normalized train-of-four (TOF) ratio of 0.9. Secondary outcomes included recovery time, time to spontaneous respiration, response to verbal commands and extubation, and adverse events. Results: The median time to achieve a normalized TOF ratio of 0.9 was 2.3 min in the R group and 2.0 min in the F group (p = 0.529). Secondary outcomes, including recovery time and time to extubation showed no significant differences. Adverse events were minimal and comparable between groups. Conclusions: The fixed-dose sugammadex (200 mg) demonstrated similar efficacy and safety to weight-based dosing (2 mg/kg) in reversing moderate neuromuscular blockade. These findings do not allow abandoning the recommendation of adjustment for body weight, particularly in patients with low body weight or comorbidities.